Determinants of Inequality in Selected SEE Countries: Results from Shapley Value Decompositions - Sebastian Leitner; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2009)
In this paper we provide a comparative analysis of inequality in household consumption per capita in four South-Eastern European countries, Albania, Bosnia & Herzegovina, Bulgaria, and Serbia. The analysis is based on a largely consistent dataset derived from the World Bank's Living Standards Measurement Study (LSMS) providing data for at least two years for each of these countries and a comparable set of variables. We apply inequality decomposition methods based on regression analysis and variants of the Shapley value approach. We also present results from related methods like a decomposition of the explained variance using different approaches for comparisons. The results suggest that three groups of variables are particularly important for explaining patterns of inequality; these are socio-demographic variables, employment status and education. Regional aspects and nationality or ethnicity plays a less important role though there are some country differences.
Keywords: C20; D63; 330; Inequality decomposition; Gini; Shapley value; Western Balkan countries